Effective Bud Induction of Acacia mangium and A. auriculiformis Without KNO3 and NH4NO3 in Media - Lin Sun; Yanping Lu; Liejian Huang (Plants)
Stem segments of Acacia mangium and A. auriculiformis containing full axillary buds were used to study the effects of reduced amounts of the main nitrogen source in the growth media. This condition, referred to as nitrogen deficiency in this article and denoted as -N, involved the omission of ammonium nitrate and potassium nitrate from MS media, and its impact on bud induction was assessed. The results show that in media lacking nitrogen, the bud induction rate, contamination rate, browning rate, stem length, and leaf number of induced buds of A. mangium and A. auriculiformis varied depending on the different culture media used. The optimal bud induction medium for A. mangium and A. auriculiformis was as follows: 1/4MS (-N) + 1.0 mg·L−1 6-BA + 0.2 g·L−1 chlorothalonil + 5 g·L−1 AGAR. The bud induction rates were 72.6% and 100.0%, respectively. There were no significant differences in the rooting rates of the induced buds between the -N treatment and the complete nutrient treatment. We found that the buds induced in the -N media did not show obvious symptoms of nitrogen deficiency, and their growth status was not significantly different from those induced in the complete nutrient media, which indicates that nitrogen is not essential for the bud induction of A. mangium and A. auriculiformis. The results of this study provide an important reference for conducting related research on other plants and have are greatly significant for the sustainable development of tissue culture technology in the future.